Targeting mitochondrial damage: shining a new light on immunotherapy - Zeng, Wenjuan; Wang, Menghui; Zhang, Yuxin; Zhou, Taicheng; Zong, Zhen (Frontiers in Immunology, 2024)
Mitochondrial damage has a particular impact on the immune system and tumor microenvironment, which can trigger cell stress, an inflammatory response, and disrupt immune cell function, thus all of which can accelerate the progression of the tumor. Therefore, it is of essence to comprehend how the immune system function and the tumor microenvironment interact with mitochondrial dysfunction for cancer treatment. Preserving the integrity of mitochondria or regulating the function of immune cells, such as macrophages, may enhance the efficacy of cancer therapy. Future research should concentrate on the interactions among mitochondria, the immune system, and the tumor microenvironment to identify new therapeutic strategies.